Pagdating sa dulo - Gomez, Rita; Vargas, Vic; Garcia, Eddie; Regal Films ([Quezon City] Frankes Films, 1971)
A taxi dancer (Rita Gomez) and taxi driver (Vic Vargas) are fished out of poverty and anonymity by a commercial film director (Eddie Garcia). The obsession with success forces them to affect images as movie stars, which suppress and eventually destroy them as persons and lovers.520
Summary from the website:https://www.imdb.com/title/tt0279305/plotsummary?ref_=tt_ov_pl
Title from container.
Screenplay and Directed, Ishmael Bernal; produced by Frankesa Films .
Rita Gomez, Vic Vargas, Eddie Garcia.
In Tagalog.
VHS
Keywords: Drama